Legal policy in controlling and supervising the governor’s regulatory (regulating) and budgetary (budgeteir) functions at the district/city level - Ampera Ariyanto (Technium Social Sciences Journal, 2024)
Article 18 paragraph (2) of 1945 Constitution Republic Indonesia shows that the relationship between provincial government and regency/city government is an equal relationship because the Governor and Regent/Mayor both run government in their respective regions based on principles of decentralization (regional autonomy) and assistance tasks. The governor has a dual position or role, namely as head of provincial region as well as Head of Region / Representative of the Central Government in region. Settle disputes in the implementation of government functions between districts / cities in 1 (one)province. Give approval to draft regency/city regulation on the formation and composition of regency/city regional apparatus, and exercise other powers in accordance with the provisions of laws and regulations the nature of authority is free authority, so in its application the governor can use discretion to make decisions and actions if regent /mayor is underperforming, does not carry out the obligations specified in laws and regulations, and violates the oath / pledge.